Math, asked by bhumikaM2081, 9 months ago

X(x-3)+2 at x=1 ,
find the value of the expression at given value of variable.

Answers

Answered by debasishbiswal790
0

Answer:

The value of the expression at given value of variable

Step-by-step explanation:

First we have to simplify the given expression

X(x-3)+2

= x²–3x+2

Now, we have to factorise it to simplify it further

= x²–3x+2

= x² –2x–x+2 {Using Identity (x+a)(x+b)=x²+(a+b)x+ab }

= x(x–2) –1(x–2)

= (x–1)(x–2)

Now for X =1

(x–1)(x–2)

= (1–1)(1–2)

= 0×-1

= 0

Similar questions